UPAYA PENCEGAHAN STUNTING PADA BALITA (LITERATURE REVIEW) STUNTING PREVENTION EFFORTS IN TODDLERS - Sri Mulia Astuti; Suryani, Lilis; Putri, Dea Ananda Putri; Arsyad, Jihan Fadilla (Andragogi Kesehatan, 2023)
Stunting is a chronic malnutrition problem caused by chronic lack of nutritional intake. Many factors cause stunting, namely low socioeconomic status, food insecurity, nutritional status of mothers during pregnancy, low birth weight, parenting, nutritional status, sanitation and water availability. This study aims to determine how to prevent stunting in toddlers. Methods, this review is carried out in stages: determining PICO questions (Problem, Intervention, Comparison, Outcome), case control, article search, assessment of relevant articles, and article analysis and synthesis. Relevant articles are searched through an electronic database, namely Google Scholar using the keyword "stunting prevention in toddlers" in Indonesian and English Twelve articles were selected based on inclusion criteria: the date of publication was 5 years old. The years 2018 to 2023 discuss "Efforts to Prevent Stunting in Toddlers". In English and Indonesian, full text, open access, and is an academic journal. In conclusion, the prevention and reduction of stunting rates is a joint responsibility of all parties, namely parents, health workers and the government. Therefore, maternal knowledge, parenting, and nutritional status are modifiable factors, while low birth weight can be prevented.